Feijão caupi submetido à inoculação com rizóbio e cultivado em latossolo do cerrado matrogrossense - Frigo, Gislane Renata (2013)
This study aimed to evaluate the productive characteristics of cowpea inoculated with rhizobia strains and grown in Oxisol of the Cerrado of Mato Grosso. Two experiments in laboratory and the other in the field were performed. The laboratory experiment consisted of phenotypic analysis of rhizobia which were used as inocula. The experiment was conducted in the experimental farm of the Federal University of Mato Grosso, campus Rondonópolis - MT, in a randomized complete block design with seven treatments, five strains of Rhizobium (four belonging to the culture collection of UFMT, and a commercial strain BR 3267), a witness to nitrogen fertilization (75 kg N ha - 1) and a control (without inoculation or mineral fertilization), with six replicates, totaling forty two experimental units . At 40 days after sowing (DAS ) were collected from six plants of the floor area of each plot to determine the variables plant height, dry weight of shoots and roots, total dry weight, number of nodules, nodule dry mass and SPAD reading and total N of roots and shoots. In corresponding to the seed formation, at 60 DAS, period SPAD reading was performed again. At the end of the cycle relative efficiency of strains of rhizobia, weight of hundred grains, total N of shoots and roots of grain and crude protein were evaluated . Data were subjected to analysis of variance and the means were compared by Tukey test at 5 % probability, using the statistical analysis program SISVAR. The results of the laboratory experiment were acceptable for all five strains tested, all developed well in relation to the parameters analyzed. Regarding the strains used in the field experiment showed that the best results for number of nodules was the C15 strain, for the determination of nitrogen in plant tissue and grain, the strain that obtained the most satisfactory results was the strain RZ23. The commercial strain BR3267 showed greater dry mass of shoots and roots. Already nitrogen control presented higher means for SPAD readings at 40 DAS, plant height of dry mass of shoot and total.14 Inoculation with rhizobia strains contributed to the development of cowpea grown in the Cerrado of Mato Grosso.